The Impact of Anxiety-Depressive Disorders in Young Adults - Hurduc (Zalum), Carmen (New Trends in Psychology, 2023)
Beyond the precise classifications of psychopathology, it is important to understand the idea that anxiety can represent both as a trait and as a condition an emotional aspect full of meanings whose understanding by each leads to integration of polarities, unlocking - paradox (or not) - balance and ultimately to unification. Embarking on the study of anxiety and depression is a challenge because the different explicit models touch on one facet of them, opening up possibilities of understanding, but also new questions. What does anxiety tell us, but depression? What do they hide? What are their mechanisms? Is it ultimately a negative or a positive aspect? Do we have to fight these anxietydepressive disorders? The paper will review the existing literature on cognitive impairment in depressive and anxiety disorders, particularly among adults. In addition, the focus of the adult age group and the effect of confounding variables on study results will be discussed. In conclusion, it can be said that cognitive-behavioral therapy of anxiety disorders is time-limited, problem-focused and based on the cognitive model of anxiety. Cognitive disorders are common in both major depression and anxiety disorders. However, more research is needed to confirm and extend these findings and to extend knowledge into clinical practice. Controlling for confounding variables in future studies is highly recommended.